BRAFV600E mutational status in thyroid carcinoma patients - single center study - Makazlieva, T; Manevska, N; Stojanoski S; Jankulovska, A; Stoilovska, B; Eftimov, A; Jovanovic, R (Springer Science and Business Media LLC, 2021)
Aim/Introduction: Thyroid carcinomas (TCs) are one of the most genetically evaluated carcinomas. The BRAFV600E mutation is the most frequent genetic alteration, but it isn`t still routinely recommended in the initial evaluation of the TCs patients. The aim of our study was to evaluate BRAF mutational status in TCs patients and to correlate it with clinical features: initial stage, age at diagnosis and post ablative 131 I scan in relation to presence or absence of BRAFV600E mutation. Materials and Methods: Fifty-two patients with TCs were evaluated for BRAFV600E mutational status from the primary tumor tissue. Retrospective analysis of the medical data and postoperative histopathology reports were performed to determine the histopathological type of tumor and the initial stage. Three nuclear medicine physicians with more than 10 years’ experience reviewed the post ablative radioiodine whole body scans (WBS). Patients were followed for average 4 years (SD ± 2.7years). Results: We found that 32 out of 52 TCs patients or 63.46% were BRAFV600E + mutation and all of them were papillary thyroid carcinomas (PTC), or 21 typical variants, 9 follicular variants and one patient each were: Warthin like, tall cell and Hurthle cell variants of PTC. BRAFV600E - were 19 (36.54%) patients (4 being follicular thyroid carcinomas and 15 patients PTC). The average age at the moment of diagnosis was similar in both groups, or 45 years ±15.25 in BRAFV600E - group and 48 ± 13.26 years in BRAFV600E + group. Regarding the initial stage in BRAFV600E - group, 55% were TNM stage I, 25% stage II, 10% stage III and 10% Stage IV and BRAFV600E + group were 53.125% Stage I, 21.875% Stage II, 21.875% Stage III and 3.125% Stage IVa. Post ablative WBS scan detected remnant thyroid tissue accumulation in all BRAFV600E + patients. In four BRAFV600E - patients the scan revealed distant metastases in 3 patients, while accumulation in neck lymph nodes in 1 patient. Conclusion: Analysis hasn’t revealed significant difference in age at diagnosis, initial staging and post ablative 131 I WBS scans among BRAFV600E + and - groups. Longer follow-up is recommended to discover the true meaning of BRAFV600E in the prognostication.